MenschenAffen - AffenMenschen Kulturgeschichte einer Mensch-Tier-Beziehung - Jacob, Frank (Beiträge zur Tiergeschichte, 2022)
Monkeys are probably the animals with which we most readily identify when it comes to recognizing the human in the animal. Nevertheless, they symbolize, as it were, a fear of human degeneration. The particular human-animal relationship is the subject of this cultural history. Frank Jacob explains what role apes played for the self-perception of humans and how they were and are understood as humanoid animals, for example as objects in research and popular media. In doing so, he sheds light on a history of relationships that continues to this day, whereby the intensity of this relationship between humans and primates has been redefined again and again over the centuries.